The changing relationship between health risk behaviors and depression among birth cohorts of Canadians 65+, 1994–2014 - Yang, Guang; D’Arcy, Carl (Frontiers in Psychiatry, 2022)
Background and objective The older adult residents of Canada form an increasingly larger proportion of the population and are becoming better educated and have more income. Depression is a common mental disorder, particularly among seniors. Several health risk behaviors - physical inactivity, tobacco use, and alcohol consumption - are linked to mental health problems. This study examines whether these health risk behaviors and their association with depression among Canadians 65+ born in eight cohorts between 1910-1914 to 1945-1949, have changed. Methods Pooled data drawn from 11 nationally representative health surveys conducted by Statistics Canada between 1994 and 2014 are analyzed - 88,675 survey participants met inclusion criteria. Depression was assessed by the Composite International Diagnostic Interview - Short Form. Health risk behaviors examined were physical activity/inactivity, smoking and alcohol use. A Cochran Armitage trend test for categorical outcomes and a log-binomial modeling for binary outcomes were used to estimate the risk ratios across cohorts. Results The proportions of Canadians 65+ who are physically active, regular drinkers, and regular smokers have increased; however, depression prevalence fluctuated non-significantly. Depression increased among all health risk behaviors, particularly in recent birth cohorts. Depression among physically inactive seniors, current smokers, and non-drinkers was significantly higher than among active, non-smokers, and regular drinkers (all P <0.05). Physical inactivity and smoking-attributable depression risk showed an increasing linear trend across birth cohorts (RR=1.67, P<0.001; RR=1.79, P<0.001). For seniors born between 1915 and 1944, regular drinking was associated with a significant decrease in depression (all P <0.001), but the protective effects of regular drinking became non-existent in the most recent 1945-1949 birth cohort (RR=1.09, P<.0.05, after adjusting for covariates). Conclusions Inactivity and smoking were consistently associated with a significantly increased risk of depression among Canadian residents 65+, with smoking becoming more firmly connected to depression risk in more recent birth cohorts. In contrast, moderate alcohol use was associated with a decreased risk of depression, but that protective effect ceased in most recent birth cohort. Identifying the changing relationships between health risk behaviors and depression is meaningful for developing prevention strategies for depression and other emotional and mental health problems.